PERLINDUNGAN HUKUM TERHADAP PRODUK PANGAN YANG TIDAK MEMENUHI SYARAT LABEL BERDASARKAN UNDANG-UNDANG NO.8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DI PROVINSI RIAU - Suryadiansyah S; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Understanding food labels according to Article 1 paragraph 3 of Government Regulation 69 of 1999 on Food Label and Advertisement is any description of the food in the form of picture writing, a combination of both, or form a food that came in, put in, attached to, or part food packaging, hereinafter in this regulation called LabelBased on this understanding, the author formulated two formulation of the problem, namely: First, how is the responsibility of businesses to the product labeling does not think large hall drug and food control. Second, whether the legal consequences for food products that do not qualify labeling great hall Food and Drug Administration.This type of research is classified in socio-juridical research, in this wear properties descriptive study using research methods that sought to describe and interpret the object in accordance with what is, with the aim of describing systematically, facts and characteristics of the object under study as appropriate. This research was conducted at the Center for Food and Drug Administration in Pekanbaru, the data used is primary data, secondary data, and data tertiary and research data collection techniques such as interviews, questionnaires and literature study.From the results, it can be concluded that, First account those who market food products to the inclusion of non-qualified labeling labels on food products is to provide a form of warnings and reprimands alone does not make businesses wary. Second, the number of food products that have been circulating in the city of Pekanbaru be a task for the Center for Food and Drug Administration to oversee the food products that have been circulating, lack of human resources that are in the Great Hall of the Food and Drug Administration in Pekanbaru be one performance bottleneck BBPOM that ineffective, and also supposed to give the sanctions more firmly to business actors.Keywords: Responsibility, Food Products, Labeling Requirements